Analysis of Factors That Influence the Success of Investigative Audits in the Public Sector - Shindy Aulia; Perisai Surbakti; Joli Valentino Simorangkir; Annisa Khairiah; Galih Supraja (CV. AFDIFAL MAJU BERKAH, 2025)
This study aims to analyze the factors that influence the success of investigative audits in the public sector. The success of investigative audits is highly dependent on several key factors, including the quality of human resources (auditors), the availability of accurate data, a supportive work environment, the use of appropriate technology, and the consistent application of audit standards. Using a qualitative approach, this research found that auditors with high competence and continuous training can improve audit effectiveness. In addition, good access to valid data, as well as a transparent and supportive work environment, facilitate the investigative process. The use of technology, such as audit software and data analytics, enhances the accuracy and speed of analysis, enabling more effective fraud detection. This study provides recommendations to strengthen public financial oversight policies to improve accountability and transparency in the public sector.